(there’s no space like home, there’s no space like home, there’s no space like home) - heath, fiona (UnderCurrents: Journal of Critical Environmental Studies, 1995)
i’m a culture hugger, a city hick, a suburban chick. (i’ve driven through algonquin park.) i’m visiting a bean-friend in cottage country. snow, ice, lake, trees, sun, birds, dean air. we walk across the singing lake, smiling at the sun, each other, the trees, until our faces hurt with pleasure. here is beauty. but cottages crowd every inch of snowmobiles soon by. electric giants hum as they march along the horizon. cars whine along the not too distant highway. this nature? is it home? what feels like nature? what feels like home? [...]